Diversity and territorial rigths in semi-arid - Costa, João Batista de Almeida (2018)
Aiming to discuss territorial diversity and rights in the brazilian semi-arid region, based on case studies, I make a reading about the historical roots of formation of the different ethnic groups and the constitution of territories in this region and then digress on the legal bases that underpin the right to diversity. It is also carried out an approach on the conceptual bases for the understanding of the emergence of collective subjects that seek to concretize the territorial rights through the visibility of its people from the self-affirmation of themselves in their territorialities. Finally, the friction of territorial interests between the upper and lower strata of the national society that opposes the diversity of appropriation and mercantile logic with cases of people from Northeast Brazil and Northern Minas Gerais is focused. And, in this case, cast strategies for the realization of the territorial law of traditional norte mineiras communities.